Parental Education, Income, and Emotional Resilience: Impact on Children with Disabilities – A Literature Review - Rezka, Fitrah Hayati Dwi; Pratama, Aditya Denny (Majalah Ilmiah Fisioterapi Indonesia; Vol 13 No 2 (2025): Majalah Ilmiah Fisioterapi Indonesia, 2025)
Introduction : Children with disabilities, such as those with Down syndrome, cerebral palsy, or autism spectrum disorder (ASD), often face complex challenges in physical, intellectual, and emotional development. Parental factors—including education level, financial status, and emotional resilience—play a crucial role in shaping the quality of life and well-being of these children. This systematic review aims to evaluate how these parental factors influence the well-being of children with disabilities. Methods : Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, relevant studies were identified through searches in Google Scholar, PubMed, Scopus, and the Cochrane Library. Inclusion criteria included studies examining the relationship between parental characteristics and quality of life outcomes among children with disabilities. Results : Higher parental education levels were associated with improved healthcare access and stronger advocacy for children’s rights. Emotional resilience in parents contributed to more effective caregiving and positive psychological outcomes in children. Moreover, better economic conditions facilitated access to healthcare and specialized educational programs, improving children’s development and overall well-being. Conclusion : The well-being of children with disabilities is significantly influenced by parental support in emotional, educational, and financial domains. Interventions should focus on empowering parents through education, mental health support, and economic strengthening to promote inclusive development for their children. Keywords : Disability; Emotional Well-being; Parental Education; Socioeconomic Factors; Quality of Life.